2008
DOI: 10.1007/s00128-008-9609-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 15 Organophosphorus Pesticides in Italian Raw Milk

Abstract: A study was conducted on raw cow's milk to measure the residues of 15 organophosphorus pesticides used as dairy cattle ectoparasiticides or as insecticides in crops used for animal feed. For this purpose a previously devised method was improved and validated. The samples were collected directly from tank trucks during delivery of 3,974 tonnes of raw milk at nine Italian dairy plants. Approximately 4.4% of the 298 samples analyzed contained residues only in traces. The main pollutant was chlorpyriphos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 7 publications
0
15
0
2
Order By: Relevance
“…A recent study of raw milk from nine Italian dairy plants found only traces of pesticide residues in approximately 4.4% of the samples analyzed. The main pollutant was chlorpyrifos (Gazzotti et al, 2009). In Mexican milk samples, the average concentrations of 13 OP pesticide residues, including chlorpyrifos, were below established MRLs and ranged between 0.0051 and 0.0203 ppm (Salas et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…A recent study of raw milk from nine Italian dairy plants found only traces of pesticide residues in approximately 4.4% of the samples analyzed. The main pollutant was chlorpyrifos (Gazzotti et al, 2009). In Mexican milk samples, the average concentrations of 13 OP pesticide residues, including chlorpyrifos, were below established MRLs and ranged between 0.0051 and 0.0203 ppm (Salas et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…(1) also used DSPE as part of fast multi-residue method of pesticide analysis in raw bovine milk, but chlorpyrifos showed recovery lower than 40%. Chlorpyrifos residues were stated as main OPP residues in raw milk, therefore the method of their determination should be characterised by a proper recovery (5). On the contrary to MSPD, DSPE, or SPE cleanup techniques, the GPC is more universal with regard to the fat content in the sample.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of pesticide residues in milk is a matter of public health concern, since milk and dairy products are widely consumed by infants, children, and adults. The presence of organophosphorus pesticide (OPP) residues in milk is still reported (5,9,13). The main causes of OPP residues in milk are carried over processes from contaminated feed, grass or corn silage, and veterinary use against parasites and insects by application of pesticides directly on the dairy cattle, in barn or in dairy plants.…”
mentioning
confidence: 99%
“…The cows can absorb these compounds by all routes (inhalation, ingestion and dermal absorption) and thus can secrete contaminated milk. [18,19] Hazardous Nature of Pesticide Residues…”
Section: Bmentioning
confidence: 99%